Hybrid Soft Soil Tire Model (HSSTM). Part I: Tire material and structure modeling. (December 2019) - Sandu, Corina; Taheri, Shahyar; Taheri, Saied; Gorsich, David
Highlights: Semi-analytical tire structure model for off-road and on-road conditions. Material modeling is presented, including viscoelastic and hyperelastic properties. The tire structure has distributed lumped masses connected by springs and dampers. The simulation platform developed is discussed. Abstract: This paper is the first of three papers describing a study focused on developing a lumped-mass discretized tire model using Kelvin-Voigt material elements. The main motivation was to develop a tire model able to capture the dynamic behavior on tire-soft soil interaction, while also being able to run on rigid (flat and rough) surfaces. This paper presents underlying mathematical formulations for characterizing the tire material properties and the kinetics and kinematics of the tire structure; the second paper focuses on the modelling of the tire-terrain interaction. The interface for connecting the tire model developed with the vehicle modeling software CarSim, in order to perform full vehicle simulations is provided. To minimize the computational time of the code, different techniques were used in stiffness matrix partitioning, parameter initialization, and multi-processing. This resulted in significant improvements for efficiency of the code making it suitable for use by commercially-available vehicle simulation packages.